Public Whipping Punishment for Adultery Offenders in Aceh: A Study on the Application of Islamic Criminal Law and International Human Rights - Fadhilah, Nurul; Samsidar, Samsidar (PT. Anagata Sembagi Education, 2025)
This study discusses the legal legitimacy of public whipping in Aceh as part of the legal specificity regulated through Law Number 11 of 2006 concerning the Government of Aceh. This specificity provides a constitutional basis for Aceh to implement Islamic law-based law through Qanun Jinayat, especially Qanun Number 6 of 2014 concerning the Jinayat Law which regulates the punishment for certain criminal acts, including adultery. Although normatively legitimate because it is underpinned by asymmetric decentralization mechanisms, the practice of public caning is controversial from a human rights perspective. Indonesia has ratified the ICCPR through Law Number 12 of 2005, so it is bound by the prohibition of cruel, inhuman, and degrading treatment. This condition creates a normative tension between Islamic sharia principles that emphasize social morality and international human rights principles that emphasize individual dignity. The research uses normative juridical methods with a legislative and conceptual approach, and analyzes the relationship between Islamic law, national law, and international law. The results of the study show the need for a more contextual reconstruction of punishment, emphasizing maqāṣid al-syarī'ah as a meeting point between religious values and human rights principles. Alternatives such as closed executions or rehabilitative punishment can be a solution so that the application of jinayat law remains relevant without causing serious contradictions. Thus, this study emphasizes the importance of humanistic, transformative, and substantive justice regulatory innovation